TINJAUAN YURIDIS PERLINDUNGAN HUKUM PEMILIK HAK ATAS TANAH TERLANTAR - Retnowati, Tutiek; Boediningsih, Widyawati (Faculty of Law, University of Dr. Soetomo, 2021)
The study is conducted to analyze the stranded soil that is alleged to be untried, unused, or abused according to the circumstances or the nature and purpose of its administration. Research methods use normative research with a regulatory approach and concept approach. This study led to the landowner's obligation to make active use of the soil. If the performance of duty towards the land is not carried out it is called wasteland. It has since built a , many there are issues involving tanah who purposefully and not do it on purpose the land has been abandoned by the owners of the the right on its own land good because economic factors the structure of the soil or allotment of that is no longer appropriate to the state of or of the nature of and the purpose of the provision of their rights . The current regulation is not currently described in detail on the criteria of land have been displaced itself . In development as abandoned land, governments must first perform identification and research processes by considering the textual and spatial data of the land and analyzing the causes of the strapless land. Legal protection for the owner of the land that is indicated to be abandoned is the granting of compensation to the land reclaimed by the state at the cost of what is already being paid by the individual, Keyword: protection of law, owner of rights to land, displaced land